Dissemination of the Media and Platforms Use to Strengthen Scientific Literacy in the Merdeka Curriculum Implementation in Elementary Schools: Diseminasi Penggunaan Media dan Platform Penguatan Literasi Sains Dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Muyassaroh, Izzah; Mufliva, Rosiana; Hartati, Tatat; Dwi Heryanto; Mulyasari, Effy; Rengganis, Ira; Heryani, Rina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract Media and platforms are important components of scientific literacy learning in implementing the Merdeka curriculum in elementary schools. This community service activity aims to disseminate the use of media and platforms to strengthen scientific literacy in implementing the independent curriculum in elementary schools. The method used is socialization, which includes several stages: identifying problems and needs, determining training topics, and evaluating. This activity was attended by 60 teachers in Kuningan Regency. In terms of process, the implementation of community service was conducive at both the online and offline stages of implementing activities. Participants were very enthusiastic about participating in question-and-answer activities, practices, and presentations on media use. All participants developed learning media and presented it in front of other participants. The success of implementing this community service is assessed from the implementation process and the output, where there is an increase in teacher understanding regarding scientific literacy and the use of media and platforms to strengthen scientific literacy skills. Keywords: science literacy media and platforms, merdeka curriculum, elementary schools Abstrak Media dan platform merupakan komponen penting pembelajaran literasi sains dalam implementasi kurikulum merdeka di sekolah dasar. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendiseminasikan penggunaan media dan platform penguatan literasi sains dalam implementasi kurikulum merdeka di sekolah dasar. Metode yang digunakan dalam kegiatan pengabdian ini yaitu sosialisasi mencakup beberapa tahapan yaitu identifikasi permasalahan dan kebutuhan, penentuan topik pelatihan, dan evaluasi. Kegiatan ini diikuti oleh 60 guru di Kabupaten Kuningan. Dari segi proses, pelaksanaan kegiatan pengabdian berlangsung kondusif dan lancar baik pada tahap pelaksanaan kegiatan daring maupun luring. Peserta sangat antusias berpartisipasi dalam kegiatan tanya jawab, praktik, dan presentasi penggunaan media. Semua peserta turut andil dalam mengembangkan media pembelajaran dan mempresentasikannya di depan peserta yang lain. Keberhasilan pelaksanaan pengabdian kepada masyarakat ini selain dinilai dari proses pelaksanaan juga dinilai dari output pengabdian dimana adanya peningkatan pemahaman guru terkait literasi sains serta penggunaan media maupun platform penguatan kemampuan literasi sains. Kata kunci: media dan platform literasi sains, kurikulum merdeka, sekolah dasar